Perancangan UI/UX B2B pada Website Harma Digital Menggunakan Metode Design Thinking - Rampalodji, Arfandy; Bezaleel, Michael; Setiawan, Arie (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2026)
Harma Digital, a company focusing on the Business-to-Business (B2B) market, recognized the urgent need for an efficient information system to facilitate service offerings online. To enhance the effectiveness and efficiency of sales, and to attract potential business partners, Harma Digital required a website platform capable of communicating its services clearly and in detail. This research aims to optimize the Harma Digital website through UI/UX design by adopting the Design Thinking methodology. This process began by gathering deep insights through interviews, a qualitative approach, to accurately reflect the specific needs of Harma Digital and its prospective clients. The results of these interviews were used to identify the main challenges and form the conceptual basis for the design. The developed UI/UX design was then refined through a series of usability tests. This testing ensured that the resulting platform was not only aesthetic but also highly functional and intuitive for B2B users. The final results indicate that the application of the Design Thinking approach successfully optimized Harma Digital's B2B website significantly. The new website improves the overall user experience and directly fosters potential partnerships and sales.